The Influence of Green Human Capital, Green Structural Capital, and Green Relational Capital on Sustainable Business Performance with Green Innovation as a Mediating Variable - Rachmawati, Ria; Risal, Zef; Qay, Nadya Salsabila; Midad, Siti Holisotul; Khusnia, Khusnia (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effects of Green Human Capital (GHC), Green Structural Capital (GSC), and Green Relational Capital (GRC) on Sustainable Business Performance (SBP), with Green Innovation (GI) as a mediating variable. The research is conducted on Small and Medium Enterprises (SMEs) in Sumenep and Bangkalan, focusing on how these green capitals contribute to sustainable business performance through innovation. A quantitative approach was adopted, involving a survey distributed to 480 SME managers across the Sumenep and Bangkalan districts. The data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess the direct and indirect relationships among the variables. The results indicate that all three green capitals—Green Human Capital, Green Structural Capital, and Green Relational Capital—positively influence Green Innovation, which in turn significantly enhances Sustainable Business Performance. The findings highlight the importance of human capital, infrastructure, and external collaborations in fostering innovation and improving business sustainability. This study integrates Green Human Capital, Green Structural Capital, and Green Relational Capital in a single conceptual model, offering novel insights into how these elements, coupled with Green Innovation, drive sustainable performance in SMEs. The study provides valuable evidence for policy recommendations, emphasizing the need for SMEs to invest in green human capital, sustainable infrastructure, and external partnerships to enhance business performance and innovation in line with sustainability goals